Genetic and Environmental Influences on Cardiovascular Disease Risk Factors: A Study of Chinese Twin Children and Adolescents. (April 2014) - Ji, Fuling; Ning, Feng; Duan, Haiping; Kaprio, Jaakko; Zhang, Dongfeng; Zhang, Dong; Wang, Shaojie; Qiao, Qing; Sun, Jianping; Liang, Jiwei; Pang, Zengchang; Silventoinen, Karri
<x content-type="archive" xml:space="preserve">Abstract</x> We evaluated the genetic and environmental contributions to metabolic cardiovascular risk factors and their mutual associations. Eight metabolic factors (body mass index, waist circumference, waist-to-hip ratio, systolic blood pressure, diastolic blood pressure, total serum cholesterol, serum triglycerides, and serum uric acid) were measured in 508 twin pairs aged 8–17 years from the Qingdao Twin Registry, China. Linear structural equation models were used to estimate the heritability of these traits, as well as the genetic and environmental correlations between them. Among boys, body mass index and uric acid showed consistently high heritability (0.49–0.81), whereas other traits showed moderate to high common environmental variance (0.37–0.73) in children (8–12 years) and adolescents (13–17 years) except total cholesterol. For girls, moderate to high heritability (0.39–0.75) were obtained for six metabolic traits in children, while only two traits showed high heritability and others mostly medium to large common environmental variance in adolescents. Genetic correlations between the traits were strong in both boys and girls in children (rg = 0.64–0.99 between body mass index and diastolic blood pressure; rg = 0.71–1.00 between body mass index and waist circumference), but decreased for adolescent girls (rg = 0.51 between body mass index and waist-to-hip ratio; rg = 0.55 between body mass index and uric acid; rg = 0.61 between body mass index and systolic blood pressure). The effect of genetic factors on most metabolic traits decreased from childhood to adolescence. Both common genetic and specific environmental factors influence the mutual associations among most of the metabolic traits.